VD_FINDINFO HC / 2012 / 697 vom 2. November 2012 - VD Tribunal cantonal (2012)
DÉCISION DE RENVOI, FRAIS JUDICIAIRES, DÉPENS | 92 al. 2 CPC, 107 al. 2 LTF, 106 al. 2 CPC (CH), 107 al. 1 let. e CPC (CH), 122 al. 1 let. b CPC (CH)